Atlas of Mohs and Frozen Section Cutaneous Pathology (Springer International Publishing, 2018)
Of all the techniques used to treat non melanoma skin cancer, the highest cure rates belong to the Mohs surgical procedure. Critical to this technique is optimal preparation and interpretation of frozen sections. The second edition of this highly successful atlas details both common and uncommon cutaneous neoplasms that can serve as a source of reference for established practitioners and a review for those in training. It includes new frozen section specimens, the most current diagnostic guidelines, and discussion of the advancements in tissue staining. There is also an additional chapter with self-study tools, where readers can test their knowledge using various images with a multiple choice answer format, followed by a discussion of the correct answer. With high resolution figures, the Atlas of Mohs and Frozen Section Cutaneous Pathology, Second Edition is the premier text on the topic, serving as a highly practical guide to microscopic analysis, diagnosis, and discrimination of common and problematic cutaneous neoplasms. Highlights of the Atlas include diagnosis of basic and routine dermatologic entities, diagnosis and distinction of rare and/or deadly neoplasms such as dermatofibrosarcoma protuberans and merkel cell carcinoma, a troubleshooting guide dealing with quality control of the frozen section technique, and discussion of techniques including immunohistochemistry. Comprehensive and presented in full color, the Atlas of Mohs and Frozen Section Cutaneous Pathology, Second Edition is an indispensable reference for anyone involved with the Mohs procedure, including dermatologic surgeons, Mohs cutaneous surgeons, as well as pathologists and dermatopathologists who perform frozen section analysis of cutaneous specimens.